Efficacy of Different Feed Additives on In Vitro Degradability of Maize Hay and Bajra Straw Based Total Mixed Ration - Patel,; Garg, Deen Dayal; K Sharma, Arun; H Savsani, Harish; A Chavda, Jignesh; M Kalam, Sanket (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was conducted to investigate the efficacy of different feed additives (Monensin T1, cellulase 10,00,000 IU/g T2, xylanase  1,50,000 IU/g T3, chitosan T4, sodium bicarbonate T5, magnesium oxide T6, combination of sodium bicarbonate + magnesium oxide  T7 and combination of cellulase + xylanase T8 added at the level of 30 mg/kg, 0.5%, 0.5%, 1%, 1%, 1%, 0.5% (Each) and 0.5% (Each)  on DM basis, respectively) on in vitro degradability of total mixed ration prepared by taking maize hay, bajra straw and concentrate in  the ratio of 30:30:40 and used as substrates for experiment. Rumen liquor was collected from two adult Surti goats 2 h post-feeding.  Statistical analysis revealed that IVDMD (%), IVOMD (%), IVNDFD (%), IVADFD (%), TDOMR (%), IVTGP (mL/200 mg), SCFAs (mMol/200  mg), ME (MJ/kg) and NE (MJ/kg) were significantly (p
Keywords: Degradability; Feed additives; In vitro; Strained rumen liquor (SRL); Total mixed ration